Unpacking the “Black Box” of Innovativeness and Innovation: Focus on Tourism Research - Catarina FERNANDES; Rui Alexandre R. PIRES (Communications of International Proceedings, 2022)
The main purpose of this paper is to provide a comprehensive analysis of innovativeness and innovation, differences and relationship, with particular focus on tourism research. The terms innovativeness and innovation are frequently used as synonyms, although they substantially differ, which leads studies to provide inconsistent and sometimes contradictory results. Innovation is an outcome of a firm´s permanent endeavor to explore and exploit new ideas. Therefore, innovativeness is a precondition for innovation. None of the previous studies, to the best of our knowledge, has provided a clear examination of them. Also, we go further and extend the analysis to the tourism industry and propose an integrative conceptual model for the study of innovativeness and innovation.
Keywords: Innovativeness; Innovation; Newness; Tourism; Performance